Sustainability-Driven Enterprise: A Literature Review on Organizational Capabilities - Viek Prayoga Pratama; Aurik Gustomo; Achmad Ghazali (Universitas Pasundan, 2022)
A sustainability-driven enterprise (SDE) is an organization that applies business principles to solve social and environmental problems. These organizations should be capable of managing the Triple Bottom Line tension within their organization. Furthermore, they should have a transformative impact on future generations and the development of global socioecological systems. The quest for an SDE and its organizational capability can be traced to the late 1980s. Since then, scholars and practitioners have published several hundred empirical studies and many reviews on this issue. However, the most extensive previous study analyzes only separate study domains, thereby making findings difficult to compare and generalize. Thus, knowledge of SDE organizational capabilities remains fragmented. This study extracts all available primary and secondary data from previous academic studies registered in the SCOPUS databases to overcome this shortcoming. Thus, the study combines the findings of more than 100 individual studies from 2015 to 2021. Hence, this study is the most exhaustive overview of academic research on this topic from the Sustainable Development Goals declared in 2015. The results show that at least five organizational capabilities are required to build an SDE. This study will offer promising fundamentals for building SDE practices and creating further research. Suggestions for further research development are also provided.